Health and social care professionals' experiences of supporting parents and their dependent children during, and following, the death of a parent: A qualitative review and thematic synthesis. (January 2019) - Franklin, Penny; Arber, Anne; Reed, Liz; Ream, Emma
Background: Children need to be prepared for the death of a parent and supported afterwards. Parents seek support from health and social care professionals to prepare their children. Support is not always forthcoming. Aim: To systematically identify, analyse and synthesise literature reporting of the experiences of health and social care professionals when supporting parents and children during, and following, the death of a parent. Design: A systematically constructed qualitative review and thematic synthesis. Registered on Prospero (CRD42017076345). Data sources: MEDLINE, CINAHL, Embase, PsycINFO, PsycARTICLES and PROSPERO, searched from January 1996 to July 2018 for qualitative studies in English, containing verbatim reporting of health and social care professionals' experiences of supporting parents and children during, and following, the death of a parent. Qualitative data were appraised using a modified Critical Appraisal Skills Programme qualitative appraisal checklist. Results: The search yielded 15, 758 articles. Of which, 15 met the inclusion criteria. A total of 13 included professionals' experiences of supporting parents and children before parental death. Two included experiences of supporting surviving parents and children afterwards. Three analytical themes identified as follows: (1) aspiring to deliver family-focussed care, (2) health and social care professionals' behaviours and emotions and (3) improving connections with parents and children. Connecting empathically with parents and children to prepare and support children entails significant emotional labour. Professionals seek to enhance their confidence to connect. Conclusion: Professionals struggle to connect empathically with parents and their children to prepare and to support children when a parent is dying and afterwards. Awareness of professionals' needs would enable provision of appropriate support for parents and children.